Pemberdayaan Mahasiswa Melalui Pelatihan Bahasa Inggris Intensif Berbasis Digital kepada Masyarakat Desa Wisata Olele - Akhmad, Zulkifli; Kai, Putri Wanda (LP2M IAIN Sultan Amai Gorontalo, 2022)
This project aims to enhance the English proficiency of residents of Olele Village, particularly those who work as tour boat guides. The participants joined three days of English Immersion led by English students of IAIN Sultan Amai Gorontalo. The participatory action research approach, abbreviated as PAR, is employed in this community service. It entails the following steps: preparation, socialization, implementation, and evaluation of activities. According to the tests and observations, the English skills of the tour boat guides in Olele village have greatly improved, rising from an average score of 50.7 (considered low) to 70.0 (considered good). Additionally, students get experience as facilitators of English language training, which they can build upon in the future.